IMPLEMENTATION OF GRAMMAR-TRANSLATION METHOD OF TEACHING FOREIGN LANGUAGES IN ENGLISH TEXTBOOKS OF BUKOVYNA (1872-1900) - Labinska, Bohdana; Tumak, Oksana (Advanced Education, 2019)
The article describes the features of teaching English in Bukovyna (a region in western Ukraine, which was a part of former Austro-Hungarian Empire) in the late 19 century and the manifestation of the European leading pedagogical ideas in English textbooks of the period. The emergence of the English language teaching methodology in Bukovyna is reflected in the school curricula of the region. The functions of foreign language textbooks are presented, which include: communicative; informational; organisational and managerial; developing and educating. English textbooks have been analysed according to these functions and criteria developed in modern methodology. The two main groups of English textbooks were differentiated: grammar references and readers. It was found that the structure and content of English textbooks corresponded to the curriculum approved by the Austro-Hungarian Ministry of Culture and Education. A lot of attention was paid to grammar material which was presented in German (the official language of the Empire) in the form of rules and commentaries; the exercises were mainly translational, reproductive and non-communicative. The reader included literary excerpts of different genres without providing pre-reading or post-reading tasks. The textbooks analysis proved the use of the approaches and principles of the grammar-translation method of teaching foreign languages which implied predominance of learning grammar, writing and translation over speaking.